2012
DOI: 10.1074/jbc.m111.291666
|View full text |Cite
|
Sign up to set email alerts
|

AMP Is an Adenosine A1 Receptor Agonist

Abstract: Background:There is no known receptor for the nucleotide AMP. Results: AMP directly activates the adenosine A 1 receptor (A 1 R) but not the adenosine A 2B receptor. Conclusion: A 1 R is a receptor for adenosine and AMP. Significance: The diverse physiological effects of AMP could be due to direct, ectonucleotidase-independent activation of A 1 R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 48 publications
7
111
2
1
Order By: Relevance
“…Very recent data obtained in transfected tumor cells indicate that AMP is a specific ligand of A1R. 28 Remarkably, 5 0 -NT appears the only enzyme responsible for extracellular degradation of AMP into Ado, 19 and its expression levels are quite low in most areas of the brain. 30 These findings suggest that the enzyme is constitutively limiting rate of Ado formation from AMP, a condition that may favor extraneuronal accumulation of the nucleotide, and ensuing A1R activation within specific brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent data obtained in transfected tumor cells indicate that AMP is a specific ligand of A1R. 28 Remarkably, 5 0 -NT appears the only enzyme responsible for extracellular degradation of AMP into Ado, 19 and its expression levels are quite low in most areas of the brain. 30 These findings suggest that the enzyme is constitutively limiting rate of Ado formation from AMP, a condition that may favor extraneuronal accumulation of the nucleotide, and ensuing A1R activation within specific brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that 5 0 -AMP can bind with a high affinity to A 1 R on HEK293 cells, 10 raising the question whether this nucleotide could deliver immunomodulatory signals to B cells. We observed that the treatment of in vitroactivated B cells with eATP plus AMPCP (a CD73 inhibitor) in order to prevent 5 0 -AMP utilization and increase its concentration in culture, did not have adverse effects on CD39 high B-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Nevertheless, these B cells inhibit T-cell proliferation and cytokine production by a mechanism presumably driven by 5 0 -AMP signaling. 14 As 5 0 -AMP was reported to be an A 1 R agonist, 10 we surmise that functions of A 1 R C T cells are inhibited not only by ADO via A 2A R but also by B cell-derived 5 0 -AMP signaling via the A 1 R. The molecular mechanisms involved in the ATP-driven suppression of T-cell functions by B cells remain poorly understood, and the identity of Breg responsible for this effect and their characteristics remain unclear. In fact, the precise Breg phenotype has been elusive and seems to be species dependent and modulated by environmental or contextual cellular interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reconstitution of CD73-deficient mice with soluble CD73 restored injury, and wild-type mice pre-treated with CD73 inhibitor were protected. We speculate that the accumulation of extracellular AMP could exert a protective effect in mild renal IRI, possibly via the A 1 R given the recent identification of AMP as a ligand for this receptor [66].…”
Section: Adenosine 1 Receptor (A 1 R)mentioning
confidence: 99%